2018
DOI: 10.1073/pnas.1721628115
|View full text |Cite
|
Sign up to set email alerts
|

Digitizing omics profiles by divergence from a baseline

Abstract: SignificanceTechnological advances enable increasingly comprehensive profiling of the molecular landscapes of cells, and these data can inform the personalized treatment of complex diseases. Two major obstacles are the complexity of these data and the high degree of person-to-person heterogeneity. We develop a highly simplified, personalized data representation by comparing the profile of an individual to the range of landscapes in a baseline population, thereby mimicking basic clinical diagnostic testing for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
51
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(51 citation statements)
references
References 30 publications
0
51
0
Order By: Relevance
“…In the above results we have showcased a variety of analyses that can be performed with divergence at the univariate and multivariate level. While we have used RNA-seq data here, the software is applicable to many other modalities of high dimensional omics data, such as microarray data, CpG level methylation data, protein data, and microRNA expression data, some of which we have showed in [1]. Once the data has been processed as necessary and the baseline cohort identified, the R package can be used to compute the divergence coding quite easily.…”
Section: Resultsmentioning
confidence: 99%
“…In the above results we have showcased a variety of analyses that can be performed with divergence at the univariate and multivariate level. While we have used RNA-seq data here, the software is applicable to many other modalities of high dimensional omics data, such as microarray data, CpG level methylation data, protein data, and microRNA expression data, some of which we have showed in [1]. Once the data has been processed as necessary and the baseline cohort identified, the R package can be used to compute the divergence coding quite easily.…”
Section: Resultsmentioning
confidence: 99%
“…For the sake of simplicity, suppose that we know whether each biomelecule is depleted, enriched, or within its normal range. This simplified framing is similar to [8], who binarize omics profiles based on divergence from baseline. In our simple setting, we may write x i ∈ {−1, 0, 1} p .…”
Section: Background and Notationsmentioning
confidence: 99%
“…This variation drives tumor progression through dysregulation of key cancer pathways and contributes to the evolutionary fitness of tumors 3,4 . Differential variability analysis of bulk transcriptional data from microarrays and RNA-sequencing have also demonstrated that tumors with worse prognosis have a corresponding increase in transcriptional variation [5][6][7][8] . Single-cell RNA-sequencing (scRNA-seq) technologies provide an unprecedented ability to measure gene expression from individual cells, enabling in-depth exploration of tumor heterogeneity 9,10 .…”
Section: Introductionmentioning
confidence: 99%